Dysbiosis and zonulin upregulation alter gut epithelial and vascular barriers in patients with ankylosing spondylitis. Issue 6 (9th January 2017) - Ciccia, Francesco; Guggino, Giuliana; Rizzo, Aroldo; Alessandro, Riccardo; Luchetti, Michele Maria; Milling, Simon; Saieva, Laura; Cypers, Heleen; Stampone, Tommaso; Di Benedetto, Paola; Gabrielli, Armando; Fasano, Alessio; et al.
Abstract : Background: Dysbiosis has been recently demonstrated in patients with ankylosing spondylitis (AS) but its implications in the modulation of intestinal immune responses have never been studied. The aim of this study was to investigate the role of ileal bacteria in modulating local and systemic immune responses in AS. Methods: Ileal biopsies were obtained from 50 HLA-B27 + patients with AS and 20 normal subjects. Silver stain was used to visualise bacteria. Ileal expression of tight and adherens junction proteins was investigated by TaqMan real-time (RT)-PCR and immunohistochemistry. Serum levels of lipopolysaccharide (LPS), LPS-binding protein (LPS-BP), intestinal fatty acid-BP (iFABP) and zonulin were assayed by ELISA. Monocyte immunological functions were studied in in vitro experiments. In addition the effects of antibiotics on tight junctions in human leukocyte antigen (HLA)-B27 transgenic (TG) rats were assessed. Results: Adherent and invasive bacteria were observed in the gut of patients with AS with the bacterial scores significantly correlated with gut inflammation. Impairment of the gut vascular barrier (GVB) was also present in AS, accompanied by significant upregulation of zonulin, and associated with high serum levels of LPS, LPS-BP, iFABP and zonulin. In in vitro studies zonulin altered endothelial tight junctions while its epithelial release was modulated by isolated AS ileal bacteria. AS circulating monocytes displayed an anergic phenotype partially restored by ex vivo stimulation with LPS+sCD14 and their stimulation with recombinant zonulin induced a clear M2 phenotype. Antibiotics restored tight junction function in HLA-B27 TG rats. Conclusions: Bacterial ileitis, increased zonulin expression and damaged intestinal mucosal barrier and GVB, characterises the gut of patients with AS and are associated with increased blood levels of zonulin, and bacterial products. Bacterial products and zonulin influence monocyte behaviour.